Antisense oligonucleotide is a promising intervention for liver diseases - Lu, Kailing; Fan, Qijing; Zou, Xiaoju (Frontiers in Pharmacology, 2022)
As the body's critical metabolic organ, the liver plays an essential role in maintaining proper body homeostasis. However, as people's living standards have increased, and with them the number of unhealthy lifestyles, the liver has become overburdened, making liver disease one of the leading causes of death worldwide. Under the influence of adverse factors, liver disease progresses from simple steatosis to hepatitis, to liver fibrosis, and finally to cirrhosis and cancer, followed by increased mortality. Until now, there has been a lack of accepted effective treatments for liver disease. Based on current research, antisense oligonucleotides (ASO), as an alternative intervention for liver diseases, is expected to be an effective treatment due to its high efficiency, low toxicity, low dosage, strong specificity, as well as additional positive characteristics. In this review, we will first introduce the design, modification, and the mechanisms of ASO, and then summarize the application of ASO in liver disease treatment, including non-alcoholic fatty liver disease (NAFLD), hepatitis, liver fibrosis, and liver cancer. Finally, we discuss challenges and perspectives in the transfer of ASO drugs into clinical use. This review therefore provides a current and comprehensive understanding of the integrative and systematic functions of ASO for its use in liver disease.